2000
DOI: 10.1177/0310057x0002800111
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Anaesthesia with the Komesaroff Vaporizer inside the Circle System

Abstract: This study assessed the safety of sevoflurane anaesthesia using two Komesaroff vaporizers inside the circle with both spontaneous and controlled ventilation. Sevoflurane concentrations were continuously monitored using a mass spectrometer and the anaesthetic depth was easily controlled. Involuntary movements occurred in eight patients and breathholding occurred in five patients after inhalational induction. With continuous monitoring of sevoflurane concentrations, induction and maintenance of anaesthesia using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 12 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…As a consequence, basal flow anaesthesia and VIC anaesthesia have become safe provided meticulous monitoring is applied. Dhara and Liu in their study of VIC sevoflurane anaesthesia using the Komesaroff vaporizer found that it was simple and safe during both controlled and spontaneous ventilation, provided that sevoflurane concentrations were continuously monitored 3 . The present study has demonstrated that it is S. P. NaNdalaN, R. J. EltRiNgham, Q. W. FaN possible to achieve both induction and maintenance of sevoflurane anaesthesia using basal flow from the outset with a VIC technique after an intravenous induction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, basal flow anaesthesia and VIC anaesthesia have become safe provided meticulous monitoring is applied. Dhara and Liu in their study of VIC sevoflurane anaesthesia using the Komesaroff vaporizer found that it was simple and safe during both controlled and spontaneous ventilation, provided that sevoflurane concentrations were continuously monitored 3 . The present study has demonstrated that it is S. P. NaNdalaN, R. J. EltRiNgham, Q. W. FaN possible to achieve both induction and maintenance of sevoflurane anaesthesia using basal flow from the outset with a VIC technique after an intravenous induction.…”
Section: Discussionmentioning
confidence: 99%
“…No difficulty in maintaining adequate sevoflurane concentrations was encountered. Dhara and Liu pointed out that the sevoflurane concentrations were steady when the volume of liquid sevoflurane in the vaporizer was between 15 to 30 ml 3 . When the residual volume was less than 15 ml higher vaporizer settings were needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the Komesaroff machine can safely delivery halothane, isoflurane or sevoflurane to anaesthetise dogs breathing spontaneously (Laredo and others 1997, 1998, 2001, Straker and others 2004). Increasing the depth of anaesthesia depresses the dogs' rate of ventilation and limits the uptake of anaesthetic vapour, which might otherwise lead to overdosage (Dhara and Liu 2000). However, this safety factor may be lost, and a dangerously high concentration of anaesthetic vapour may be delivered, when mechanical ventilation is applied (Jordan and Bushman 1981, White 1985, Dhara and Liu 2000).…”
mentioning
confidence: 99%
“…The use of a draw-over vaporiser positioned in-circuit (VIC) has been well described [1][2][3][4][5][6] , but when controlled ventilation is used there are significant concerns about the risk of an unpredictable output leading to overdose. Most VIC and low-flow studies have been done using Komesaroff or Goldman vaporisers.…”
mentioning
confidence: 99%